Winner effects and switching assessment strategies facilitate fast and frugal decisions in territorial contests - Dinh, Jason; Azza, Joshua; Patek, S.N. (Dryad, 2020)
Animals compete in contests over limited resources, and contestants with
greater fighting ability, or resource holding potential (RHP), typically
win contests. Contest strategies have evolved to balance contest costs
with the benefit of winning resources. Sometimes, contestants decide to
leave by estimating their opponent’s relative RHP . This strategy (mutual
assessment) is cost-effective because it allows weaker opponents to leave
contests against formidable opponents before accruing higher costs.
However, acquiring reliable information can be costly. Here, we showed
that in snapping shrimp contests, contestants assessed relative RHP
quickly and costeffectively by assessing their opponent’s recent contest
success. By staging 26 contests between randomly matched individuals and
24 contests between RHPmatched individuals, we determined that snapping
shrimp assessed their opponent’s RHP during initial contest phases but no
longer assessed relative RHP during escalated phases. Then, after staging
24 contests between individuals with contest experience the day prior, we
found that snapping shrimp integrated RHP and recent contest success to
make contest decisions. This strategy facilitated fast and accurate
judgments when the recent winner was also larger but often resulted in the
larger individual retreating when facing a small recent winner. Notably,
these systematic biases were corrected when RHP differences were stark.
Taken together, our findings demonstrate that by assessing recent contest
success early in a contest, snapping shrimp can avoid risky contests.
Furthermore, by integrating recent contest success with direct
observations of RHP, contestants avoid losing contests prematurely.
Similar assessment strategies may be widespread, because they circumvent
risky contests while minimizing premature defeats from weaker recent
winners.
Keywords: FOS: Biological sciences